(untitled) (Research, Society and Development, 2022)
The new coronavirus (SARS-CoV-2) pandemic brought an unimaginable health and humanitarian crisis to humanity, in addition to the need to rethink our way of life in society. The objective of this paper was to present data on the evolution of the pandemic in South America and the first confrontation measures adopted by governments, highlight the importance of scientific dissemination and demonstrate how social inequalities, especially in traditional vulnerable communities, can further impact small isolated populations. The exploratory study used secondary data from scientific articles, legal regulations, and informational and/or official communications, in relation to the advance of the SARS-CoV-2 pandemic in the South American continent. The results showed the importance of science in the dissemination of measures to prevent the spread of SARS-CoV-2, the need for a prioritization and logistical plan for vaccination and disease prevention in traditional vulnerable communities, and that the lack of access to connectivity, as an alternative to educational actions in a moment of social isolation, can further increase social inequalities. It was concluded that environmental education can directly contribute to the democratization of scientific information, collaborate in the construction of strategies to face the pandemic in South American countries in partnership with Governments and Non-Governmental Organizations, and facilitate the resumption of social and educational activities, seeking the construction of inclusive public policies and environmental justice, besides reducing inequalities.